Adobe Illustrator CS6 : learn by video (Learn by video., 2012)
"This innovative product from Adobe Press and video2brain combines exceptional quality interactive video and a full-color printed reference to teach the fundamentals of Illustrator CS6. Experienced instructors present 10 hours of high quality HD video, complete with project files so viewers can practice what they've learned, as well as a printed book that provides supplemental material to enhance the video training."--Resource description page.